Clinical assessment of hand oedema: A systematic review. (December 2017) - Miller, Leanne K; Jerosch-Herold, Christina; Shepstone, Lee
Introduction: Assessment of oedema after trauma or surgery is important to determine whether treatment is effective and to detect change over time. Volumetry is referred to as the 'gold standard' method of measuring volume. However, this has practical limitations and other methods are available. The aim of this systematic review was to evaluate the psychometric properties of alternative methods used to assess hand oedema. Methods: A search of electronic bibliographic databases was undertaken for any studies published in English reporting the psychometric evaluation of a method for measuring hand oedema, in an adult population with hand swelling from surgery, trauma or stroke. The Consensus‐based Standards for the Selection of health Measurement Instruments (COSMIN) checklist was used to evaluate the methodological quality. Results: Six studies met the inclusion criteria. Three methods were identified assessing hand oedema: perometry, visual inspection and the figure-of-eight tape measure, all were compared to volumetry. Four different psychometric properties were assessed. Studies scored fair or poor on COSMIN criteria. There is low-quality evidence supporting the use of the figure-of-eight tape measure to assess hand volume. The perometer systematically overestimated volume and visual estimation had poor sensitivity and specificity. Discussion: The figure-of-eight tape measure is the best alternative to volumetry for hand oedema. Benefits include reduced cost and time while having comparable reliability to the 'gold standard'. Further research is needed to compare methods in patients with greater variability of conditions and with isolated digit oedema. Visual estimation of hand oedema is not recommended.